Evaluation of the OsTIR1 and AtAFB2 AID Systems for Genome Architectural Protein Degradation in Mammalian Cells - Yunusova, Anastasia; Smirnov, Alexander; Shnaider, Tatiana; Lukyanchikova, Varvara; Afonnikova, Svetlana; Battulin, Nariman (Frontiers in Molecular Biosciences, 2021)
Auxin-inducible degron (AID) system is a promising tool for dynamic protein degradation. In mammalian cells, this approach has become indispensable to study fundamental molecular functions, such as replication, chromatin dynamics or transcription, that are otherwise difficult to dissect. We present evaluation of the two prominent AID systems based on OsTIR1 and AtAFB2 auxin receptor F-box proteins (AFBs). We analyzed degradation dynamics of cohesin/condensin complexes subunits in mouse embryonic stem cells (Rad21, Smc2, Ncaph, Ncaph2) and human haploid HAP1 line (RAD21, SMC2). Double antibiotic selection helped achieve high homozygous AID tagging of an endogenous gene for all genes using CRISPR/Cas9. We found that the main challenge for successful protein degradation is obtaining cell clones with high and stable AFB expression levels due to mosaic expression of AFBs. AFB expression from transgene tends to decline with passages in the absence of constant antibiotic selection, preventing epigenetic silencing of a transgene, even at the AAVS1 safe-harbor locus. Comparing two AFBs, we found that OsTIR1 system showed weak dynamics of protein degradation. At the same time, AtAFB2 approach was very efficient even in random integration of AFB expressed transgene. Other factors such as degradation dynamics and low basal depletion were also in favor of AtAFB2 system.